Understanding fishery interactions and stock trajectory of yellowfin tuna exploited by Iranian fisheries in the Sea of Oman. (15th June 2021) - Eighani, Morteza; Cope, Jason M; Raoufi, Paria; Naderi, Reza Abbaspour; Bach, Pascal
Abstract: The predominant policy for remedying the world fishing crisis aims at maximum sustainable yield (MSY) by adjusting gear selectivity and fishing effort to maintain sustainable stock levels. The yellowfin tuna ( Thunnus albacares ) fishery in the Sea of Oman has experienced intense increases in removals since 1980, with particularly high levels since the 1990s. Here, we apply a statistical catch-at-age model to time-series of catches and fishery-dependent length composition data to obtain a preliminary and general understanding of the population dynamics of this stock since the start of the fishery in 1950–2019. Despite limited data, population models consistently indicate a sharp decline in population status since the beginning of the time-series across a variety of assumptions on stock productivity and life history. The gillnet fishery takes almost exclusively immature individuals, with high fishing intensity and removal rates. Both reference models indicate the population is essentially at the same relative stock status in 2019 (10% of unfished), but with very different future projections and higher absolute stock size when recruitment is estimated. The yellowfin tuna population in 2019 is below estimated MSY reference points (based either on unfished size or spawning output at MSY) for current relative stock size, and over the fishing intensity at MSY, indicating current overfishing. Adjusting the interactions of that fishery with the population, while continuing to collected biological composition data representative of each fleet in the fishery, will help mitigate current stock decline and provide the ability to refine future population status determination and forecasts through more informed stock assessments.